Age-Specific Reference Intervals for PT, aPTT, Fibrinogen and Thrombin Time for Parturient Women - Zhang, Gao-Ming; Zhang, Wei; Zhang, Guo-Ming (Thrombosis and Haemostasis, 2019)
Background Parturient women are healthy individuals who require special consideration. Parturient women are considered to be in a hyper-coagulable state. For example, the fibrinogen (FIB) levels are often higher than the upper limit of normal reference intervals (RIs) in parturient women than in non-parturient healthy individuals (2–4 g/L).Objective The aim of this study is to establish the RIs of pro-thrombin time (PT), activated partial thromboplastin time (aPTT), FIB levels and thrombin time (TT) for parturient women.Materials and Methods Blood levels of PT, aPTT, FIB and TT were assayed on an ACL TOP 700 automatic coagulation analyser using plasma samples from 10,472 parturient women. Outlier results were excluded by using Tukey's test. The RIs were calculated by the Clinical and Laboratory Standards Institute C28-A3 guideline.Results The RIs of PT, aPTT, FIB and TT were 8.7 to 12.1 seconds (8.7–12.2 seconds for 16–20 years old, 8.7–12.1 second for 21–25 years old, 8.6–12.0 second for 26–30 years old, 8.7–12.0 second for 31–35 years old, 8.7–12.6 second for 36–40 years old and 8.8–12.2 second for 41 years old), 22.9 to 42.3 seconds, 1.98 to 5.82 g/L and 9.9 to 16.7 seconds, respectively. PT levels were found to be positively associated with aging.Conclusion The above-established age-specific RIs, defined by using a large dataset, may assist clinicians in making accurate medical decisions. This was the first study in which the RIs of PT, aPTT, FIB and TT were established for parturient women in different age groups.
Keywords: reference intervals; parturient women; pro-thrombin time; thromboplastin time; activated partial thromboplastin time